Erratum: Pharmacokinetic and pharmacodynamic characteristics of a new pediatric formulation of artemether-lumefantrine in African children with uncomplicated Plasmodium falciparum malaria - Djimdé, Abdoulaye A.; Tekete, Mamadou; Borrmann, Steffen (ASM journals, 2012)
Volume 55, no. 9, p. [3994-3999][1], 2011. Page 3999, column 1, line 4: “P. K. Klouwenberg” should read “P. Klein Klouwenberg.” [1]: /lookup/doi/10.1128/AAC.01115-10